PENGARUH KOMPOSISI BAHAN BAKU MASSA COR CN (CN2, CN3, CN6, CN7, CN8) TERHADAP TEKNOLOGI PROSES DAN VARIABEL KEUANGAN PADA UPT PSTKP BALI-BPPT - Ni Nyoman Nurani (STIMI Handayani Denpasar, 2016)
Abstracts: The aims of this are to know the influence of CN casting massa raw materialcomposition to technology process, cost of goods manufactured calculation, transferprice determination, inventory valuation, operating expense and operating profitrecognition. The research results shew that: (1) the production process technologyCN casting massa follow by: weighting, grussing, mixing, filtring, and carrying.On the weighting process, the greater amount of composition and/or kinds of rawmaterial, the more complex and longer of weighting process. The raw materialcomposition influenced process technology CN casting massa superior on weightingprocess; (2) the cost of good manufactured CN casting massa was Rp 2.896,83 forCN2, Rp 3.031,83 for CN3, Rp 3.017,00 for CN6, Rp 3.004,52 for CN7, and Rp2.996,50 for CN8. (3) the transfer price CN casting massa composition was Rp3.302,39 for CN2, Rp 3.456,28 for CN3, Rp 3.473,58 for CN6, Rp 3.425,15 for CN7,and Rp 3.416,01 for CN8. (4) the ending inventory CN casting massa compositionwas Rp 434.524,50 for CN2, Rp 454.774,50 for CN3, Rp 457.050,00 for CN6, Rp450.678,00 for CN7, and Rp 449.475,00 for CN8. (5) the marketing expense CNcasting massa was Rp 173,81 for CN2, Rp 181,91 for CN3, Rp 182,82 for CN6, Rp180,27 for CN7, and Rp 179,79 for CN8. (6) The operating profit CN casting massa was Rp 115,87 for CN2, Rp 121,27 for CN3, Rp 121,88 for CN6, Rp 120,18 for CN7,and Rp 119,86 for CN8.